2021
DOI: 10.4018/ijcewm.2021010102
|View full text |Cite
|
Sign up to set email alerts
|

The Circular Economy, Resilience, and Digital Technology Deployment in the Mining and Mineral Industry

Abstract: The mining and mineral industry is not easily associated with sustainable development. The one is focused on the exploitation of the planet's limited natural resources, while the other attempts to promote development that meets the needs of the present without compromising the needs of future generations. This article looks at the industry's approach to the core sustainability concepts of the circular economy and resilience and finds that leading companies in this industry have drawn on the concept of resilien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Zaid et al (2018) Prior literature tends to support a positive association between GPP and ECOP (Altaf et al, 2020;Pinto, 2020). However, researchers have also found negative/insignificant results in their studies (Çankaya & Sezen, 2019;Jones & Wynn, 2021;Sahoo & Vijayvargy, 2021;Zhu et al, 2017). These mixed findings motivate us to conduct this study lead to the study of the relationship among these variables.…”
Section: Green Purchasing Practices and Economic Performancementioning
confidence: 85%
“…Zaid et al (2018) Prior literature tends to support a positive association between GPP and ECOP (Altaf et al, 2020;Pinto, 2020). However, researchers have also found negative/insignificant results in their studies (Çankaya & Sezen, 2019;Jones & Wynn, 2021;Sahoo & Vijayvargy, 2021;Zhu et al, 2017). These mixed findings motivate us to conduct this study lead to the study of the relationship among these variables.…”
Section: Green Purchasing Practices and Economic Performancementioning
confidence: 85%
“…Khan et al [19] found that fossil fuels reduced and renewable energy improved the environmental quality in Europe. Moreover, bulk literature has suggested that the concept of a circular economy and green business practices would serve to promote eco-environmental performance [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…They developed the viability of a biological system (that is similar to the intertwined supply network) by a dynamic model of the game theory approach. Jones and Wynn ( 2021 ) studied the resilience and sustainability aspects of the circular economy in the mining and mineral industry and revealed that the most important firms in this industry have applied the resilience concept in their sustainability strategies.…”
Section: Literature Reviewmentioning
confidence: 99%